THE HUMAN RIGHTS FACE OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN MEXICO: HOW FAIR IS THE REALITY? - Barrios Garrido, Gabriela (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2005)
Historical socio-economic factors together with an inefficient judicial system, non-autonomous, non-accountable public human rights institutions are some of the problems nullifying the WSIS Declaration of Principles and Plan of Action. Formally, contemporary Mexico is a global human rights player with respect to human rights instruments promoting equality, dignity, respect and protection of human rights and the rule of law, but the gap between reality and the so called goals and statements of the government remains significant. In December, 2003, the Office of United Nations High Commissioner for Human Rights presented the Mexican government with an analysis of the human rights situation in Mexico to serve as a road map for government policy on human rights issues, as well as issues concerning the judiciary and information and communication technologies (ICT). The digital gap goes hand in hand with the phenomenon of poverty in which individuals live in conditions of vulnerability, insecurity, discrimination, with no possibility of exercising their civil and political rights. The opportunities provided by ICT tools are still in the hands of the privileged whose main interest is financial gain. Capacity building and ICT literacy are pertinent. The discrepancy between the governmental programs to bridge the digital divide and the results in indicators for accessing ICTs is clear. The government’s most ambitious project, which aims to connect citizens to the information society, needs to be re-thought, or it will continue to fail. A legal data protection framework for the private sector is still in being developed. Some universities and the Senate have done analyses of ICTs in relation to the Tunisia 2005 WSIS meeting, but there seems to be only political marketing and no effective governmental interest in implementing the WSIS Declaration of Principles and the Plan of Action.